Strategi Penguatan Usaha dan Pemahaman Laporan Keuangan Bagi UMKM Kota Tegal - Ghea Dwi Rahmadiane; Nurul Mahmudah; Yusri Anis Faidah; Sadiva Kayla Tasya (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
This activities are focused on strategies to strengthen businesses and understand financial statements for UMKM. Some of them have basic needs, onion farmers, salted egg business and some even have small businesses such as handicrafts, batik, ducks, and others. This shows the potential for entrepreneurship and the development of UMKM that are quite large. Nevertheless, the existing UMKM have not yet developed optimally due to the lack of knowledge regarding business strengthening strategies and understanding of financial statements. The objectives of community service activities include increasing and strengthening the efforts of UMKM entrepreneurs in Tegal City, increasing understanding of financial reports for UMKM in Tegal City, and introducing the existence of Polytechnic Harapan Bersama Tegal who cares and has social responsibility on the condition of the community, especially the UMKM in the Tegal City of the Tri Dharma Perguruan Tinggi. This activity was held in the Margadana Village in Tegal City on 26-27 July 2021 and was attended by 20 UMKM in Maradana Kelurahan in Tegal City. This activity was welcomed positively by Margadana Village and the village felt the need for such counseling especially for UMKM, because an understanding of financial reports and strategies for strengthening UMKM was needed.